Educational Dualism in Indonesia: Systematic Literatur Review - Hidayati, Nurul; Muhid, Abdul; Sahri, Iksan Kamil (Jurnal Tarbiyatuna, 2023)
Dualism in education is an interesting topic to discuss. Two entities separated as a result of this educational dualism are not easy to be united. However, this situation has happened, and what we have to do is finding the solution to anticipate the effects of the dualism. This article uses SLR method, which aims to summarize researches that have been done on history, effects, and solution of educational dualism in Indonesia. In this Systematic Literature Review (SLR) we collect, synthesize, and analyse research articles on educational dualism in Indonesia published between 2013 and 2023. The result of the research is that educational dualism in Indonesia is caused by several respects. First, this dualism is started from the policy of the Dutch Colonial Government in the pre-independence era. Second, the dualism is inherited and rooted up to now. Third, there is a political factor in the Indonesian government. Fourth, government policies that is considered weakening and alienating madrasah education (Islam), Fifth, the narrowness of scientific studies in Islamic education. Meanwhile, the impacts of this dualism are that there is a dichotomy in knowledge, the cost of education is unaffordable for the lower middle class, curriculum development is increasing but religious, cultural and social values are experiencing a decline, and the world of education is becoming a political playing ground. To reduce the impact of the educational dualism above, several solutions are offered: one, eliminating scientific dichotomies; two, awakening the Islamic scientific ethos and scientific integration; three, changes in government policy.